RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

pH-responsive metal–organic framework–iron scaffolds for antibacterial and osteogenesis-promoting applications in diabetic infected bone defects - Yaxin Xue; Xinyu Ran; Danyang Zhao; Jian Wang; Hao Jiang; Chengji Wang; Wei Xu; Hao Lv; Zhencheng Yu; Zijing Du; Yi Cao; Dongmei Dong; et al. (Chemical Engineering Journal, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Recent advances in the design mechanisms of mitochondrial fluorescent probes: A review - Fei Peng; Bo Wang; Yunjia Xu; Ran Chai; Aibing Wu; Mingming Xue; Huijuan Tian; Yan Lv; Xiangyu Guo; Bin Hao; Baoxiang Gao (Analytica Chimica Acta, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Unraveling the dual impacts of damming and eutrophication on dissolved organic carbon dynamics in a large River - Hao Wang; Xiaosong Zhong; Xiaotian Liu; Zongqing Lv; Xiangbin Ran (Journal of Hydrology, 2026)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Tissue-specific responses and interactive characteristics of crop-microbe "One Health" system to soil chromium and ofloxacin pollution - Jia-Min Xu; Yaru Zhang; Kai Wang; Guodong Zhang; Ying Liu; Hao-Ran Xu; Hu-Yi Zi; Ai-Jie Wang; Yao Lv; Kun Xu; Hao-Yi Cheng (Process Safety and Environmental Protection, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)